2016
DOI: 10.1002/etc.3402
|View full text |Cite
|
Sign up to set email alerts
|

Local and interannual variations in mercury and cadmium in eggs of eight seabird species of the Sinaloa coast, México

Abstract: Mercury (Hg) and cadmium (Cd) concentrations in eggs of 8 seabird species inhabiting 5 coastal ecosystems in Sinaloa, México were determined during 2 breeding seasons (2012 and 2013): blue-footed booby (Sula nebouxii), brown booby (Sula leucogaster), double-crested cormorant (Phalacrocorax auritus), magnificent frigatebird (Fregata magnificens), brown pelican (Pelecanus occidentalis), royal tern (Thalasseus maximus), laughing gull (Leucophaeus atricilla), and Heermann's gull (Larus heermanni). The interspecifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…García-Hernández et al (2006) evaluated the concentration of Cd and Pb in eggs and embryos (in different stages) of aquatic birds living in the Colorado River Delta (Sonora) and found concentrations of 0.13-0.78 and 0.06-0.20 µg g -1 dw for Cd and Pb respectively. Similarly, Ceyca et al (2016) reported values of 1-1.6 µg g -1 dw for Cd in seabird eggs in the coastal zone of Sinaloa, similar values to those found in the muscle tissue of several seabirds collected in the Altata-Ensenada de Pabellón Lagoon (Sinaloa), with concentrations of 0.2-1.6 µg g -1 dw, which suggests that a high percentage of this contaminant is transferred via the mother.…”
Section: Cadmium and Lead In Biotasupporting
confidence: 71%
See 2 more Smart Citations
“…García-Hernández et al (2006) evaluated the concentration of Cd and Pb in eggs and embryos (in different stages) of aquatic birds living in the Colorado River Delta (Sonora) and found concentrations of 0.13-0.78 and 0.06-0.20 µg g -1 dw for Cd and Pb respectively. Similarly, Ceyca et al (2016) reported values of 1-1.6 µg g -1 dw for Cd in seabird eggs in the coastal zone of Sinaloa, similar values to those found in the muscle tissue of several seabirds collected in the Altata-Ensenada de Pabellón Lagoon (Sinaloa), with concentrations of 0.2-1.6 µg g -1 dw, which suggests that a high percentage of this contaminant is transferred via the mother.…”
Section: Cadmium and Lead In Biotasupporting
confidence: 71%
“…All cases of Hg in fish muscle reviewed here were below this concentration. In birds, Ceyca et al (2016) indicated that Hg concentrations of 0.5-1 µg g -1 ww in sea bird eggs could cause mortality, malformations, and neurological damage. Ceyca et al (2016) also reported maximum Hg values of 0.55-187 µg g -1 ww in eight species of seabirds collected on the coast of Sinaloa.…”
Section: Effect Of Pbtss On Aquatic Organisms and Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Trace elements are typically differentiated into two categories: essential elements required for important processes within organisms, and non-essential elements that are not required for any biological purpose and are therefore particularly toxic when they accumulate within organisms (Burger, 1993;Ceyca et al, 2016;Moura et al, 2018). Several trace elements are of particular concern due to the concentrations released into the environment, as well as the documented toxicological effects at relatively low concentrations.…”
mentioning
confidence: 99%
“…In the marine environment, three elements (Hg, Pb, and Cd) have been extensively studied because they bioaccumulate and biomagnify in aquatic food webs (Burger, 1993). Exposure can harm species in a variety of ways, including impaired biological function of proteins, enzymes, and cell damage (Burger, 1993;Ceyca et al, 2016). These impacts are often demonstrated using marine birds as sentinels, or bioindicators, as apex predators can also provide information on broader ecosystem health (Borghesi et al, 2016;Durant et al, 2009).…”
mentioning
confidence: 99%